Hand Hygiene Practices Reported by Nurse Aides in Nursing Homes. (March 2016) - Castle, Nicholas; Handler, Steven; Wagner, Laura
Information from nurse aides describing their opinions of hand hygiene practices in nursing homes including perceived barriers to hand hygiene is presented. The information comes from a questionnaire developed for this investigation, with items addressing compliance, facility guidelines and protocols, training, hand washing facilities and materials, and hand washing barriers. Information from 4, 211 nurse aides (response rate of 56%) working in a nationally representative sample of 767 nursing homes (participation rate = 51%) is used. We find that 57.4% of nurse aides comply with hand washing when caring for residents most of the time, while 21.7% always comply. With facilities, 43.3% sometimes check that hand washing is performed. In summary, self-reported compliance was poor, and facilities and materials were often lacking. These findings are useful in identifying issues and interventions, including the need for further initiatives to address hand hygiene practices.